Role of Work Discipline Mediation on Work Motivation and Employee Performance: Study of Agriculture and Food Security Office of Pandeglang Regency - Setiawati, Firda; Mukhsin, Moh; Kambara, Roni; Imron, Ali; Harun, Asro bin (Journal of Business Management and Economic Development, 2025)
The purpose of this study was to test and analyze the role of work discipline mediation on employee motivation and performance (Study of the Agriculture and Food Security of Pandeglang Regency). This study was carried out at the Office of Agriculture and Food Security of Pandeglang Regency using descriptive quantitative methods with a causal approach. Respondents of this study were all civil servants at the Pandeglang Regency Agriculture and Food Security Office, using a sample of 174 respondents. Questionnaire answers were measured using an interval scale of 1 - 10. Data analysis using SmartPLS software version 4.1.0.8. The results of research and hypothesis testing show that: (1) Work Motivation has a positive and significant effect on Employee Performance (2) Work Motivation has a positive and significant effect on Work Discipline (3) Work Discipline has a positive and significant effect on Employee Performance (4) Work Discipline can mediate the relationship between Work Motivation and Employee Performance.